Pronominal Description of Poguli - Wani, Neelofar Hussain (LANGUAGE ART, 2019)
Poguli is spoken in the Pogal-Paristan area of district Ramban in the state of Jammu and Kashmir (India). Poguli shows interesting and significant variations from Kashmiri in phonology, morphology, and vocabulary, but linguistic research on these aspects of the dialect of Kashmiri has been inadequate and fragmentary. Limited work has been done on Poguli and is mostly based on oral form. The present paper attempts to study Poguli on morphological description basis. The study shall include description of pronouns of Poguli in question. It aims to give a complete account of different features of pronouns in Poguli.